Does road safety cointegrate with socio-economic conditions in rich developing countries? - Ibrahim Abdalla Alfaki; Michal Grivna; Mohamed El Sadig (PLoS ONE, 2026)
Despite significant progress in road safety in developed countries, it remains a persistent and critical challenge in the developing world. This study investigates the long- and short-term relationships between socio-economic conditions and road safety performance in affluent developing countries, using the United Arab Emirates (UAE) as a case study. Employing an autoregressive distributed lag (ARDL) cointegration error-corrected model with data from 1980 to 2024 (sourced from the UAE Federal Government, the World Bank, and UN World Population Prospects), the analysis examines the link between the road crash severity index (fatalities to total injuries) and core socio-economic variables—GDP per capita, unemployment rate, and population density—while controlling for traffic law enforcement via fines. The findings confirm a long-term equilibrium, with an error correction term indicating road safety adjusts to socio-economic shocks at a rapid annual rate of 60%. Granger-causality tests further establish that these socio-economic factors significantly influence road safety outcomes, a concern underscored by an identified upward trend in crash severity. We conclude that socio-economic conditions are a fundamental determinant of road safety, highlighting the necessity for policy interventions that move beyond traditional engineering solutions. Consequently, road safety must be reframed not solely as a transportation concern but as an integral objective of public health and socioeconomic policy, which requires a collaborative, multi-sectoral approach to forge a resilient, safe system.